Adopsi TIK di DPR RI: Analisis TAM dan Pelajaran dari Parlemen Inggris - Ardiyanti, Handrini (Jurnal Pekommas, 2024)
This study analyzes the adoption of Information and Communication Technology (ICT) in the Indonesian House of Representatives through the lens of the Technology Acceptance Model (TAM) and draws lessons from the UK Parliament. The analysis is divided into four parts: 1) Historical context and policy framework of ICT adoption in the Indonesian House of Representatives; 2) Policy and strategy of ICT adoption in the Indonesian House of Representatives; 3) Best practice from the UK Parliament; and 4) Challenges of Big Data Management in the Indonesian House of Representatives. The study provides an in-depth understanding of ICT adoption in the Indonesian House of Representatives and valuable lessons from the UK Parliament experience to enhance ICT adoption effectiveness. Study conclusions include: 1) The importance of a Big Data system, particularly for bill digest summaries; 2) The early stage of ICT adoption in the Indonesian House of Representatives; 3) Prioritization of bill digest availability to enhance public engagement in the legislative process; 4) Crucial collaboration with state institutions for Big Data integration, aligned with the national one data initiative. The Indonesian House of Representatives plays a central role in providing legislative data in Indonesia.